124k views
5 votes
Write an equation for the following tile pattern.

Figure 2

Figure 3

Figure 4

Write an equation for the following tile pattern. Figure 2 Figure 3 Figure 4-example-1

1 Answer

6 votes

Answer:

The general equation following the pattern becomes is 7 + (n - 1)×2

Where, n = The figure number - 1

Explanation:

The pattern in the question can be described as follows;

Figure 2 = (5 + 2) squares boxes = 7 squares boxes

Figure 3 = (5 + 2 + 2) squares boxes

Figure 4 = (5 + 2 + 2 + 2) squares boxes

Therefore, the number of squares boxes per figure, form an arithmetic progression (a + (n - 1)d) with the first term a = 7, the common difference d = 2, and the n = the nth term of the series, such that the general equation following the pattern becomes;

7 + (n - 1)×2.

User Harri Siirak
by
7.5k points